Sub‐Lithospheric Small‐Scale Convection Tomographically Imaged Beneath the Pacific Plate. Issue 18 (26th September 2022) - Eilon, Zachary C.; Zhang, Lun; Gaherty, James B.; Forsyth, Donald W.; Russell, Joshua B.
Abstract: Small‐scale convection beneath the oceanic plates has been invoked to explain off‐axis nonplume volcanism, departure from simple seafloor depth‐age relationships, and intraplate gravity lineations. We deployed 30 broadband ocean bottom seismometer stations on ∼40 Ma Pacific seafloor in a region notable for gravity anomalies, measured by satellite altimetry, elongated parallel to plate motion. P ‐wave teleseismic tomography reveals alternating upper mantle velocity anomalies on the order of ±2%, aligned with the gravity lineations. These features, which correspond to ∼300°–500°K lateral temperature contrast, and possible hydrous or carbonatitic partial melt, are—surprisingly—strongest between 150 and 260 km depth, indicating rapid vertical motions through a low‐viscosity asthenospheric channel. Coherence and admittance analysis of gravity and topography using new multibeam bathymetry soundings substantiates the presence of mantle density variations, and forward modeling predicts gravity anomalies that qualitatively match observed lineations. This study provides observational support for small‐scale convective rolls beneath the oceanic plates. Plain Language Summary: Covered by kilometers of water and therefore hard to access, Earth's oceanic tectonic plates have several features we cannot explain. Among these are linear undulations ("rolls") in the strength of gravitational acceleration at the sea surface. Using data from a rare underwater seismic experiment, we have produced 3‐D maps of seismic properties of the Earth's sub‐surface in a location of clear gravity rolls. We find linear blobs of fast and slow material in the mantle beneath the oceanic plate, parallel to the gravity features. These represent cold sinking and warmer rising material, revealing a highly dynamic convective system underneath the plate, which has long been theorized but not previously directly observed at this scale. Key Points: We use ocean bottom seismometer data to image elongated upper mantle P ‐wave velocity anomalies, of order ±2%, striking parallel to free air gravity lineations These features extend >200 km deep, requiring thermal anomalies and small‐fraction partial melts related to volatiles in the asthenosphere Anomalies are inferred to arise from small‐scale convective cells beneath the plate with a planform parallel to absolute plate motion